An Exploration of the Influence of Arithmetic Thinking Ability, Qur’anic Reading Fluency, and Learning Environment on the Quality of Juz ‘Amma Memorization among PGMI UMALA Students - Isnaini Nur Azizah; Muhammad Nur Amin; Hanif Amrulloh; Ahmad Zarnuji; Kiki Abelia; Rizki Asrarul Mufidah (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2025)
Memorizing the Qur'an is a tradition that dates back to the time of the Prophet. Over time, this trend has gradually entered the realm of formal education. The Qur’an is the only holy book memorized by tens of millions of people. The quality of memorization is influenced by various factors, such as arithmetic thinking ability. Arithmetic thinking skills can help huffaz (those who memorize the Qur’an) calculate how long it will take to complete their memorization if they recite a certain number of pages daily, or determine how many pages must be memorized per day to meet a specific yearly target. The second factor is fluency in reading the Qur’an. The fluency level of huffaz in reading the Qur’an also affects the quality of their memorization. Another important factor is the learning environment. This study aims to identify and examine empirical data regarding the influence of arithmetic thinking ability, Qur’anic reading fluency, and learning environment on the memorization quality of Juz ‘Amma among PGMI UMALA students, both partially and simultaneously. The research sample consisted of 30 respondents from a total population of 236 PGMI UMALA students. Data collection methods included questionnaires, interviews, observations, and documentation. The analysis used was both statistical and descriptive.